2016
DOI: 10.1016/j.rehab.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Post-acute referral of stroke victims in a French urban area: Results of a specific program

Abstract: Patients that were assessed were more likely to be transferred to specialized rehabilitation units than to non-specialized rehabilitation units. The Post-Acute Stroke program has the particularity of combining private and public specialized rehabilitation units in a common collaborative referral system while retaining the control and flexibility of personalised referral for each patient in the light of local care availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
4
0
4
Order By: Relevance
“…Coordenação do Cuidado/Pode ser benéfico explorar minuciosamente as expectativas dos pacientes antes da alta, pois certos sentimentos e pensamentos podem interferir neste processo. Cassoudesalle H et al 2016/França (16) Coorte IV Coordenação do Cuidado/Destaca o valor de uma organização coerente em nível local entre os diferentes parceiros do setor de saúde tanto público quanto privado.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Coordenação do Cuidado/Pode ser benéfico explorar minuciosamente as expectativas dos pacientes antes da alta, pois certos sentimentos e pensamentos podem interferir neste processo. Cassoudesalle H et al 2016/França (16) Coorte IV Coordenação do Cuidado/Destaca o valor de uma organização coerente em nível local entre os diferentes parceiros do setor de saúde tanto público quanto privado.…”
Section: Resultsunclassified
“…Em relação ao período de publicação dos estudos, não houve destaque relacionado aos últimos anos. O predomínio de estudos ocorreu em 2016 (16)(17)(18)(19) e 2019 (22)(23)(24)(25) , com quatro artigos em cada ano.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Studies have reported LOS after stroke in Spain (64.1 days), in the United States [16 days (acute inpatient rehab hospital), 28 days (skilled nursing facility)] ( 24 , 25 ). Although a direct comparison cannot be made, the mean LOS for patients with stroke who were admitted to the rehabilitation wards was 16.8 days (the United States), 22.7 days (China), 24.3 days (Taiwan), 30.8 days (Singapore), 41.7 days (Canada), 54.5–76.3 days (France) ( 26 31 ). In Japan, the mean LOS from the time of stroke onset to the home discharge is more than 100 days, which is similar to that of Korea ( 32 ).…”
Section: Transitional and Long-term Rehabilitation Care Systemmentioning
confidence: 99%